Improving IMU-Based Prediction of Lower Limb Kinematics in Natural Environments Using Egocentric Optical Flow - Abhishek Sharma; Eric Rombokas (IEEE, 2022)
We seek to predict knee and ankle motion using wearable sensors. These predictions could serve as target trajectories for a lower limb prosthesis. In this manuscript, we investigate the use of egocentric vision for improving performance over kinematic wearable motion capture. We present an out-of-the-lab dataset of 23 healthy subjects navigating public classrooms, a large atrium, and stairs for a total of almost 12 hours of recording. The prediction task is difficult because the movements include avoiding obstacles, other people, idiosyncratic movements such as traversing doors, and individual choices in selecting the future path. We demonstrate that using vision improves the quality of the predicted knee and ankle trajectories, especially in congested spaces and when the visual environment provides information that does not appear simply in the movements of the body. Overall, including vision results in 7.9% and 7.0% improvement in root mean squared error of knee and ankle angle predictions respectively. The improvement in Pearson Correlation Coefficient for knee and ankle predictions is 1.5% and 12.3% respectively. We discuss particular moments where vision greatly improved, or failed to improve, the prediction performance. We also find that the benefits of vision can be enhanced with more data. Lastly, we discuss challenges of continuous estimation of gait in natural, out-of-the-lab datasets.